Nursing Gender Pay Differentials in the New Millennium. Issue 1 (8th November 2017) - Wilson, Barbara L.; Butler, Matthew J.; Butler, Richard J.; Johnson, William G.
Abstract: Background: The gender pay gap in the United States is an ongoing issue, affecting women in nearly all occupations. Jobs traditionally associated with men tend to pay better than traditionally female‐dominated jobs, and there is evidence to suggest within‐occupation gender pay differences as well. Purpose: We compared and contrasted gender wage disparities for registered nurses (RNs), relative to gender wage disparities for another female‐dominated occupation, teachers, while controlling for sociodemographic factors. Methods: Using data in the American Community Survey, we analyzed the largest U.S. random representative sample of self‐identified RNs and primary or secondary school teachers from 2000 to 2013 using fixed‐effects regression analysis. Results: There is greater disparity between nurse pay by gender than in teacher pay by gender. In addition, the net return in wages for additional education is higher for school teachers (21.7%) than for RNs (4.7%). Conclusions: Findings support preferential wages for men in nursing, more so than for men in teaching. Clinical Relevance: The substantial gender disparities are an indirect measure of the misallocation of resources in effective patient care.